PROFIL MAQ?SID AL-SYAR?AH (Upaya Membendung Paham Radikalisme dan Mempertahankan NKRI) - H. Fathurahman (Al-Bayyinah, 2017)
AbstractThis research discusses about the profile of Maq?sid al-Syar?ah. This research aims to stem radicalism ideology using Islamic moderate doctrine or Islam wasa?iyah. This research is also intended to defend The Unitary State of the Republic of Indonesia using priority settlement. This research uses library research. The technique of data collection is finding out some related books and references in the library. Further, the data is compiled systematically. The approach the researcher used is historical, sociological, and usul fiqh. The result of this research shows that the comprehension and impression towards al-dar?r?t al-khamzah are supposed to stem radicalism. Further, the concept of al-masalih} al-sal?sah is also expected to streghten The Unitary State of the Republic of Indonesia as well.Kata Kunci: Maq?sid al-Syar?ah, Radikalisme, NKRI